Design and indicator system of the statistical survey on functional and foundational learning skills of children living in Georgian households - Mikeladze, Giorgi (Edelweiss Applied Science and Technology, 2025)
This paper aims to design and implement a statistical survey to assess the functional and foundational learning skills of children aged 7–14 living in Georgian households. It also focuses on developing a methodology for calculating the wealth index and internationally comparable indicators such as the overcrowding rate. The study employed a three-stage stratified cluster random sampling design, involving 3,597 households across 193 clusters. Survey instruments were adapted from reputable sources including UNICEF, Eurostat, and the Washington Group on Disability Statistics. To ensure representativeness and comparability, five types of statistical weights were calculated. The construction of the wealth index utilized factor and regression analysis, while indicators related to Sustainable Development Goals, such as SDG 4.1.1a and 4.5.1, were derived from the data. The overall household response rate was 56.9%, with the target group response rate reaching 99.9%. The study revealed that 6.6% of children experienced functional difficulties, and 62.1% of the household population live in overcrowded housing, a rate that exceeds Eurostat averages. The wealth index distribution demonstrated significant disparities between urban and rural households. The survey methodology proved to be statistically reliable, producing robust indicators on children’s education, functional skills, and living conditions. The findings provide valuable evidence for shaping education policy, teacher training, and social inclusion strategies. Additionally, the study enables Georgia to align with international statistical standards and SDG monitoring requirements, supporting sustainable development efforts across the country.